Do Voting Advice Applications Affect Party Preferences? Evidence from Field Experiments in Five European Countries - Germann, Micha; Mendez, Fernando; Gemenis, Kostas (My University, 2023)
Voting advice applications (VAAs) are online tools that provide voters with personalized information on the extent to which their policy views match those of political parties or candidates. These tools have proliferated across advanced democracies in recent years and become integral parts of electoral campaigns, especially in multi-party systems. However, it remains unclear to what extent voters actually make use of VAAs to inform their voting preferences. We present new field-experimental evidence on the short-term effects of VAAs on party preferences from five European countries. We find consistent evidence that exposure to VAA advice leads voters to update their party preferences in line with the information provided. Furthermore, we find partial evidence that VAAs more strongly influence less politically interested and undecided voters. Overall, our results point to the potential value of VAAs as a mechanism to strengthen democratic representation and accountability.
Keywords: Voting advice applications; Party preferences; Democratic representation; Issue voting; Field experiment